Estimation of Performance Improvement Derived from TCP/IP Offload Engine with Software Emulation - Nishijima, Takamichi; Yokoi, Nobuhiro; Nakamoto, Yoichi; Ohsaki, Hiroyuki (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Many TOE (TCP/IP Offload Engine) devices have been developed and installed in high-end systems.Â Although there have been many analysis of the effectiveness of TOE devices, there remain open issues related to them.Â For example, it has not been clarified which part of TCP/IP processing should be performed with hardware and which with software, or how end-to-end TCP/IP performance is affected by the introduction of a TOE device.Â In this paper, we propose VOSE (Virtual Offloading with Software Emulation), which is a technique for measuring TCP/IP performance improvements derived from different type of TOE devices without implementing TOE prototypes really.Â VOSE enables virtual offloading without requiring a hardware TOE device by virtually emulating TOE processing on both source and destination end hosts.Â For demonstrating the effectiveness of VOSE, we apply VOSE to the TCP checksum and IPsec protocol.Â We extensively examine the accuracy of virtual offloading with VOSE, by comparing performance (i.e., end-to-end performance and CPU processing overhead) between VOSE and a dedicated TOE device.Â Moreover, we estimate performance improvement that are derived from several TOE devices of IPsec and combinations of those devices, by applying VOSE to header authenticating and payload encryption in IPsec protocol.Â Consequently, we show that performance improvements which are derived from TOE devices can be estimated correctly.